Gynecological and breast cytopathology board review and self-assessment - Means, Marilee; Khalbuss, Walid E. (Springer New York, 2013)
Gynecological and Breast Cytopathology Board Review and Self-Assessment is a comprehensive systems-based review of gynecological and breast cytology including cytomorphology, pitfalls and ancillary studies. Presented in a high-yield format with board-type multiple choice questions and detailed answers, this review includes chapters covering Pap smear cytology, colposcopy, breast FNA, and Pelvic washings. The book is also enriched with features to maximize studying and reviewing of cytopathology, including high-yield review with tables emphasizing key points, board exam-type questions, and high quality full-color images.   Written by cytologists and cytopathologists with experience in the practice of modern cytology, as well as intensive teaching experience at national and international levels. Gynecological and Breast Cytopathology Board Review and Self-Assessment provides an excellent review, resource, and self-assessment for pathologists, cytopathologists, cytotechnologists, and trainees preparing for board examinations.